ISLAMIC NEW MEDIA AGAINST GLOBAL PROPAGANDA (THE ANTITHESIS OF GENDER RELATIONS IN THE ISLAMIC WORLD) - Al Muroji Panjaitan; Ahmad Sujai Tanjung; Mailin Mailin (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2021)
ABSTRACT Gender is the differentiation of roles, attributes, traits, attitudes and behaviors that grow and develop in society. And gender roles are divided into productive roles, reproductive roles and social roles. Gender can be defined as the roles formed by the community and the behavior that is embedded through the socialization process related to the gender of women and men. There are biological differences between women and men—but culture interprets these biological differences into a set of social demands about appropriateness of behavior, and in turn rights, resources, and power within each individual. While these demands vary by society, there are some striking similarities. For example, almost all community groups hand over responsibility for child care to women, while military duties are assigned to men. Like race, ethnicity, and class, gender is a social category that largely determines a person's way of life and participation in society and the economy. Not all societies experience discrimination based on race or ethnicity, but all societies experience discrimination based on gender—in the form of inequalities and differences—to varying degrees. It often takes a long time to change this injustice. This atmosphere of injustice can sometimes change drastically because of the policies and socio-economic changes experienced during the Global Propaganda period in Indonesia. Keywords: New Media, Gender Relations, Islamic World